Evidence-Based Science Communication - Jensen, Eric A.; Gerber, Alexander (Frontiers in Communication, 2020)
Effective science communication can empower research and innovation systems to address global challenges and put public interests at the heart of how knowledge is produced, shared, and applied. For science communication to play this mediating role effectively, we propose a more integrated and ‘evidence-based’ approach. This commentary identifies key issues facing the science communication field. It suggests a series of prescriptions, inspired by the impact of ‘evidence-based medicine’ over the past decades. In practice, evidence-based science communication should combine professional expertise and skills with the best available evidence from systematic research. Steps required to achieve this outcome include more quality assurance in science communication research, significant changes in teaching and training, and improved interfaces between science communication research and practice.